2015
DOI: 10.1063/1.4913361
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of hydration in Y2Mo3O12: Effects on structure and negative thermal expansion

Abstract: We report ab-initio calculations of water absorption in Y2Mo3O12. The absorption geometry of H2O in Y2Mo3O12 and the binding property between H2O and Y2Mo3O12 have been first identified. Our calculated results show that water is chemisorbed in Y2Mo3O12 with O of the water binding to the Y3+ cation, which is further strengthened by hydrogen bonding between each of the hydrogen atoms of H2O and the bridge O in Y2Mo3O12, shared by polyhedrons YO6 and MoO4. The absorption of water leads to a reduced angle of Y-O-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Marinkovic et al showed that the water molecules occupy microchannels with diameter around 5 Å along c-crystallographic directions in Y 2 (MoO 4 ) 3 structure, leading to a negative thermal expansion in Y 2 (MoO 4 ) 3 [38]. Furthermore, M. Wu et al showed that the water absorption reduces the Y-Mo bond distance, shortening the Y-O-Mo bond angle and consequently reducing the solid volume [41].…”
Section: Resultsmentioning
confidence: 99%
“…Marinkovic et al showed that the water molecules occupy microchannels with diameter around 5 Å along c-crystallographic directions in Y 2 (MoO 4 ) 3 structure, leading to a negative thermal expansion in Y 2 (MoO 4 ) 3 [38]. Furthermore, M. Wu et al showed that the water absorption reduces the Y-Mo bond distance, shortening the Y-O-Mo bond angle and consequently reducing the solid volume [41].…”
Section: Resultsmentioning
confidence: 99%
“…The HRTEM image and the diffraction fringes reflect the real status of the hydrated Y 2 Mo 3 O 12 Á3H 2 O because the crystal waters are not physically adsorbed but are chemically bonded. 22,24 The regular lattice diffraction fringes indicate no lattice distortion in the sample, i.e. fully hydrated Y 2 Mo 3 O 12 Á3H 2 O still presents a periodic structure but the space group is different from the unhydrated Y 2 Mo 3 O 12 reported by Lind et al 20,23 It can be inferred that fully hydrated Y 2 Mo 3 O 12 Á3H 2 O with the space group Pba2 is the most energetically favorable form, and that lattice distortion will occur during the release of crystal water and it will eventually become unhydrated Y 2 Mo 3 O 12 with the space group Pbcn.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Molybdates with a general formula A 2 Mo 3 O 12 family, where A is a trivalent cation, are known to be hosts for transition metal ions and lanthanide ions [1][2][3]. Recently, these materials have attracted lots of attention because of negative thermal expansion (NTE), characterized by chemical exibility and a phase transition, from monoclinic to orthorhombic, depending on the A 3+ cation size [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these materials have attracted lots of attention because of negative thermal expansion (NTE), characterized by chemical exibility and a phase transition, from monoclinic to orthorhombic, depending on the A 3+ cation size [4][5][6][7][8]. These NTE materials are microporous and interstitial cation-free frameworks consisting of vertex-linked AO 6 octahedra and MO 4 tetrahedra, where each AO 6 octahedron joins MO 4 tetrahedra sharing oxygen of their corners [1,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation